Transforming the void: embryological discourse and reproductive imagery in East Asian religions - Andreeva, Anna; Steavu-Balint, Dominic (Sir Henry Wellcome Asian series, 2015)
Preliminary Material -- Introduction: Backdrops and Parallels to Embryological Discourse and Reproductive Imagery in East Asian Religions /Anna Andreeva and Dominic Steavu -- 1 Prenatal Infancy Regained: Great Peace (Taiping) Views on Procreation and Life Cycles /Grégoire Espesset -- 2 Conceiving the Embryo of Immortality: “Seed-People” and Sexual Rites in Early Taoism /Christine Mollier -- 3 Cosmos, Body, and Gestation in Taoist Meditation /Dominic Steavu -- 4 Symbolic Pregnancy and the Sexual Identity of Taoist Adepts /Catherine Despeux -- 5 Creation and Its Inversion: Cosmos, Human Being, and Elixir in the Cantong Qi (The Seal of the Unity of the Three) /Fabrizio Pregadio -- 6 On the Effectiveness of Symbols: Women’s Bodies as Mandalas /Brigitte Baptandier -- 7 The Embryonic Generation of the Perfect Body: Ritual Embryology from Japanese Tantric Sources /Lucia Dolce -- 8 Buddhism Ab Ovo: Aspects of Embryological Discourse in Medieval Japanese Buddhism /Bernard Faure -- 9 “Human Yellow” and Magical Power in Japanese Medieval Tantrism and Culture /Nobumi Iyanaga -- 10 “Lost in the Womb”: Conception, Reproductive Imagery, and Gender in the Writings and Rituals of Japan’s Medieval Holy Men /Anna Andreeva -- 11 Embryology in Early Modern Sōtō Zen Buddhism /Kigensan Licha -- 12 Foetal Buddhahood: From Theory to Practice – Embryological Symbolism in the Autumn Peak Ritual of Haguro Shugendo /Gaynor Sekimori -- Index /Anna Andreeva and Dominic Steavu.